(untitled) (REGE Revista de Gestão, 2013)
The management of interpersonal conflict becomes complex in the context of public organizations, and especially in education. Becomes necessary then to evaluate the processes of interpersonal conflict management in these institutions, mainly because the interpersonal relationships and commitment are vital elements in the quality and effectiveness of the educational process. From this discussion, this research aims to understand how the civil servants dealing with this phenomenon. For this, we will seek to clarify some points about the main types of conflict, its causes, forms of management used and its impacts. Then, we performed a field survey in two public institutions of vocational education from Nova Iguacu, the Unidade de Ensino Descentralizada de Nova Iguaçu of CEFET/RJ and Escola Técnica Estadual João Luiz do Nascimento. Thus, interviews were conducted with its servers and further analysis of content, which could conclude that there aren´t mechanisms for conflict management in these organs, this being done on a personal management, besides corroborating sources of conflict discussed in theory. We also conclude that the studied organizations interpersonal conflicts can impact work relationships.